First-Principles Study on Hydrogen Storage Performance of Transition Metal-Doped Zeolite Template Carbon - Bai Han (Crystals, 2019)
The hydrogen adsorption characteristics and mechanism of transition metal-doped zeolite template carbon (ZTC) as a novel porous material are studied by theoretical calculations employing first-principle all-electron atomic orbital method based on density functional theory. The stability of transition metal atoms (Sc, Ti, and V) decorated on zeolite template carbon is investigated by calculating the absorption binding energy. The adsorption configurations of the doped metal atom and adsorbed hydrogen are obtained from the energy functional minimization of first-principles calculations. The underlying mechanism for improving hydrogen storage performance of ZTC by doping transition metal atoms are explored through analyzing charge/spin populations of metal atoms in combination with the calculated results of hydrogen adsorption quantity and binding energy. To improve the hydrogen storage capability, the Sc, Ti, and V are individually introduced into the ZTC model according to the triplex axisymmetry. The hydrogen storage properties of ZTC decorated with different metal atoms are characterized by the adsorption energy and structure of several hydrogen atoms. The more energetically stable complex system with higher binding energy and adsorbing distance of hydrogen than lithium-doped ZTC can be achieved by doping Sc, Ti, V atoms in ZTC, which is expected to fulfill the substantial safe hydrogen storage by increasing hydrogen capacity with multi-sites doping of transition metal atoms. The present investigation provides a theoretical basis and predictions for the following experimental research and design of porous materials for hydrogen storage.